Improving Student’s Eco-Literacy Skills Through the Use of The Eco-Literacy Module - Rana Gustian; Fasli Jalal; Endry Boeriswati (Universitas Djuanda, 2022)
This research is motivated by the low level of eco-literacy of elementary school students. This study aims to improve students' eco-literacy skills by using the eco-literacy module. The method used in this study is an experimental method with the object of research being 40 students The sample chosen was 40 respondents consisting of 18 male students and 22 female students of Karangsambung III State Elementary School, Kadipaten District, Majalengka Regency, West Java Province. The instrument used tests and non-tests, to measure knowledge consisting of 20 questions, and to measure attitudes used attitude observation sheets, and the psychomotor instrument used performance tests. Data analysis techniques in this study used the independent sample t-test with a significance level of 0.05. In addition, to find out how much the level of effectiveness of using the eco-literacy module has on students' ecological abilities, the researchers conducted the Cohen's d test. The results showed that the use of the eco-literacy module could improve the eco-literacy ability of elementary school students. The increase in ability is influenced by the activities of students and teachers in the learning process in the classroom. The eco-literacy module has a positive impact on students so that students become enthusiastic about learning so they don't feel bored when studying the material. Based on the research results, other schools need to implement eco-literacy-based learning modules in an effort to form better ecological literacy and the ability to solve environmental problems